KEWIRAUSAHAAN MERUBAH MINDSET TARUNA SEBAGAI ALTERNATIF SOLUSI JOB SEEKER MENJADI JOB CREATOR DI POLITEKNIK PENERBANGAN SURABAYA - Ariyono Setiawan; Laila Rochmawati; Heri Sudarmaji; Yuyun Suprapto; Sri Rahayu Surtiningtyas; Ahmad Bharawi (Jurnal Penelitian)
Changes in one's thinking about entrepreneurship tend to be influenced by factors of interest and readiness; job seekers become job creators. The mindset paradigm of the cadets/cadets of the Vocational School of Transportation in Indonesia is attached to the official pattern; ready to work immediately after graduation. However, empiricism shows that cadet graduates are faced with the opposite conditions. This course is designed to provide knowledge, skills and abilities to cadets regarding the development of entrepreneurial concepts, the role of creativity, innovation and various intelligences in entrepreneurship as well as matters related to preparation for become entrepreneurs Under these conditions, graduates are required to have other abilities in order to be able to compete in the world of work, for example the ability to become entrepreneurs. The role of educators is needed to change the mindset of graduates with job seekers to become job creators. To achieve this goal, the role of education is needed through the development of an entrepreneurship curriculum. Based on the research results, it will contribute directly to the preparation of the entrepreneurship education learning curriculum at the Air Transportation Vocational School. Thus, the practical implications related to the findings of this research are its application at the policy and operational levels and the authors contribute to preparing Air Transportation Vocational School graduates capable of entrepreneurship as a career alternative to compete in the world of work.